Career Pause in Long-Term Earning Implications in Iraq and Its Relevance to the Principles of Islamic Economic Law - Nurkanbek PATIEV; Thabit Abdull Majeed Turki HUMADI; Maan ALI; Fadhil Jawad DAHASH; Mustafa Jabbar AHMED; Wafaa Adnan Sajid; Saad Qasim Abbas; Ali Akram Kadhim; Noor Ali SULIMAN (al-'adalah, 2025)
This study examines the long-term impact of prolonged career breaks on workers’ earnings in Iraq and its relationship to the principles of Islamic economic law. This study is conducted in the context of a growing trend worldwide where individuals take unpaid leave for personal reasons (e.g., health, family, education). The study evaluates the economic impact of a six-month career break through a mixed-methods approach, using fixed-effects regression models, in addition to qualitative interviews. Using a hypothetical framework that combines classical accounting theories, market orientation, and Islamic economic law principles, the study provides a multidimensional analysis of labor dynamics in Iraq. The results indicate that breaks accompanied by significant salary reductions are inconsistent with the principles of Islamic economic law that emphasize the balance between individual welfare (maslahah), social justice (‘adl), and labor equity. These findings highlight the need for socio-economic policies with an Islamic character to protect income stability, facilitate employee reintegration, and prevent gender bias in employee career advancement.